The evaluation of operational performance of supply chain at automotive industry - Gholampour, Gholamreza (Asian Research Publishing Network, 2015)
Todays, Supply Chain Management is one of the most important and complex issues for automakers in the world. The main objectives of this research are to explore the factors to predict operational performance of the supply chain (OPSC) through survey and case study research in IRANKHODRO Company (IKCO). Based on the supply chain theories, previous studies and structural equation modeling operational performance of the supply chain was predicted by process innovation (PI) and partnership quality (PQ). In addition, the relationship between IT and OPSC was moderated by process innovation and the positive effect of IT on OPSC was rejected. A total numbers of 217 completed questionnaires were collected from IKCO. The reliability of data was evaluated by using SPSS to analyse Cronbach’s alpha, where all values of alpha were acceptable strongly. According to SEM, measurement and structural model were analyzed to evaluate validity and hypothesizes. The confirmatory factor analyses (CFA) were utilized based on the Maximum Likelihood (ML) to examine model. OPSC model was examined for the first time in the automotive industry, which as the research gap was concluded. This research contributes to focus on IT, PQ, PI and OPSC as theoretical, managerial and practical implications.